2014
DOI: 10.1038/onc.2013.565
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and consequences of constitutive NF-κB activation in B-cell lymphoid malignancies

Abstract: The discovery of constitutive nuclear factor-κB (NF-κB) activation in Hodgkin's lymphoma tumor cells almost two decades ago was one of the first reports that directly connected deregulated NF-κB signaling to human cancer. Subsequent studies demonstrated that enhanced NF-κB signaling is a common hallmark of many lymphoid malignancies, including Hodgkin lymphoma, mucosa-associated lymphoid tissue lymphoma, diffuse large B-cell lymphoma and multiple myeloma. By inducing an anti-apoptotic and pro-proliferative gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
105
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(109 citation statements)
references
References 150 publications
4
105
0
Order By: Relevance
“…Moreover, NF-κB is considered as one of the major mediators linking chronic inflammation and malignant transformation of cells [7,9,10]. NF-κB is constitutively active in most types of cancer, and many signaling pathways, involved in carcinogenesis, are accompanied by this factor activation [10,11].…”
Section: Abstract:paclitaxelthyroidanaplasticcancerapoptosimentioning
confidence: 99%
“…Moreover, NF-κB is considered as one of the major mediators linking chronic inflammation and malignant transformation of cells [7,9,10]. NF-κB is constitutively active in most types of cancer, and many signaling pathways, involved in carcinogenesis, are accompanied by this factor activation [10,11].…”
Section: Abstract:paclitaxelthyroidanaplasticcancerapoptosimentioning
confidence: 99%
“…In order to further investigate the mechanisms of TSA action, the influence of TSA on the activation of NF-κB was determined, since it has been suggested that NF-κB is involved in the development and progression of various malignant neoplasms (27)(28)(29)(30)(31)(32)(33), which made it a target for tumor therapeutics (34,35). The present data revealed that 20 µM TSA treatment significantly decreased the level of phosphorylation of p65, a subunit of NF-κB (Fig.…”
Section: Involvement Of Nuclear Factor-κb (Nf-κb) In Tsa Activitymentioning
confidence: 87%
“…The results of the present study confirmed the antitumor activity and chemosensitizing effect of TSA in colon cancer cells and provided new evidence that TSA can sensitize colon cancer cells to 5-FU through the suppression of NF-κB activation. NF-κB is constitutively activated in numerous human cancer types (30)(31)(32)35). The suppression of NF-κB may induce apoptosis and sensitize cancer cells to chemotherapy (33,34,47,48).…”
Section: Discussionmentioning
confidence: 99%
“…In the past the amount of proteins found in the urine, taken as an indicator of the underlying abnormality in glomerular permeability, was considered by most nephrologists simply as a marker of the severity of renal lesions. Today the results of many studies indicate that proteins filtered through the glomerular capillary may have intrinsic renal toxicity, which together with other independent risk factors such as hypertension, can play a contributory role in the progression of renal damage [1,5]. Indeed, the secondary process of reabsorption of filtered proteins can contribute substantially to renal interstitial injury by activating intracellular events, including up-regulation of vasoactive and inflammatory genes, apoptosis activation.…”
Section: Discussionmentioning
confidence: 99%
“…The most common form of NF-κB is RelA(P65)/p50 heterodimers, which are generally retained inert in the cytoplasm by the inhibitor protein, I-kappaB (IκB). Following stimulation of the cell by a variety of agents, IκB is degraded, allowing NF-κB to translocate to the nucleus and bind to the promoter regions of its multiple target genes [4,5]. The molecular mechanisms underlying irreversible renal damage in children with nephrotic syndrome depending on apoptosis activation might be a potential therapeutic issue its treatment.…”
Section: Introductionmentioning
confidence: 99%